Serous Cystadenoma of the Pancreas With Complex Florid Papillary Architecture: A Case Report and Review of the Literature. (December 2019) - Tracht, Jessica; Reid, Michelle D.; Hissong, Erika; Sekhar, Aarti; Sarmiento, Juan; Krasinskas, Alyssa; Xue, Yue
Serous cystadenoma (SCA) is a relatively rare benign pancreatic neoplasm. It has a very distinctive gross and microscopic appearance including pure and mixed microcystic and macrocystic patterns as well as rare solid architectural pattern. In this article, we present a rare case of SCA with a complex florid papillary architecture. A 40-year-old man was diagnosed with a 3.5 cm SCA of the uncinate process of the pancreas based on abdominal computed tomography scan. The tumor was monitored radiographically until recent magnetic resonance imaging showed a new 1.0-cm eccentric mural nodule within the tumor with multiple arterial enhancing septations and features suspicious for a neuroendocrine tumor. A pylorus-preserving Whipple procedure was subsequently performed and the mass was resected. Gross examination confirmed the radiological findings of a well-demarcated, 3.5 cm multicystic pancreatic lesion with a 1.0 cm circumscribed, tan solid nodule at its periphery. Microscopic evaluation revealed a predominantly microcystic pattern classical of SCA with occasional macrocysts. The 1.0 cm discrete nodule was also a SCA, but showed unusually exuberant complex papillary growth. To our knowledge, this is the first reported case describing this morphologic variant. Recognition of this rare and unusual pattern is important to avoid misdiagnosis, especially on small biopsy specimens.